Governance, development and conflict - Chatterji, Manas, 1937-; Gopal, Darvesh; Singh, Savita (Contributions to conflict management, peace economics and development ;, 2011)
Over the last three decades, a considerable amount of work has been conducted in the field of peace studies, conflict management, peace science in economics, sociology, anthropology and management. This volume presents up-to-date, cutting-edge research by respected scholars with an emphasis on theoretical and mathematical constructs in the area of peace economics & peace science.